PERGESERAN MAKNA LEKSIKAL KOSAKATA ISLAM PADA TERJEMAHAN ROBOHNYA SURAU KAMI KARYA AA NAVIS - , TRYA INDRANINGSIH; , Yuni Wachid Asrori, S.S., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis analysed the problem of meaning shifts on ì°ë¦¬ ì¬ìì ë¶ê´´ (Uri sawonui bunggwoe) short story translation. This short story was a translation of Robohnya Surau Kami by A.A Navis. The purpose of this research is to know the Islamic concept words which had the meaning shifts on ì°ë¦¬ ì¬ìì ë¶ê´´ short story translation. Besides, the other purpose of this research is to find the factors of the meaning shifts and the gradation of shifts. The theory used in this research was lexical equivalency theory from Catford. The method that was used in this research was to compare SL text with TL text from Zuchridin Suryawinata and Sugeng Hariyanto. Every Islamic concept words on ì°ë¦¬ ì¬ìì ë¶ê´´ short story translation had an analysis for their meaning shift. Some example of Islamic concept words in this research âmengajiâ, ânerakaâ, âfitrah Idâ, âberibadatâ, âbedukâ, âkafanâ, âsembahyangâ, âhajiâ. Those words translated to âê³ì¨ì ì§í¤â (gyeyureul jiki), âì§ì¥â (jiok), âìì¼ì¡°â (sibiljo), âë§¹ì¸íë¤â (maengsehada), âë¶â (buk), âììâ (suui), âê¸°ëíë¤â (gidohada), âíì§â (haji) on the TL. Then those results of translation were analysed by comparing them with the original text of Robohnya Surau Kami. Based on the analysis of this research, there were meaning shifts on ì°ë¦¬ ì¬ìì ë¶ê´´ short story translation. Those meaning shifts consist of the meaning shift from specific to generic, the meaning shift from generic to specific and the meaning shift caused by the different point of view of culture. Those happened because of the limitation of words and the culture differences. It also can be concluded that the gradation of shift which happened included the shift with high readability, error interpretation of the meaning, untranslatability.